Analisis Pengaruh Kemudahan Pengguna Terhadap Efektivitas Alat Kompresi Sampah Botol Plastik “Bottlepress” Berbasis IoT - Shinta Arafah Hidayanti; Nur Aziezah; Hikmah Rahmah; Walidatush Sholihah; Inna Novianty (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
The purpose of this study was to determine the influence of users and the effectiveness of the Plastic Bottle Waste Compression Tool "Bottlepress" as an innovation in protecting the environment. The method used is a quantitative survey form using the Google Form platform in the form of a questionnaire to obtain a sample. Simple Linear Regression and Correlation methods were used as data analysis of this study.  The results of this study indicate that there is no influence between user convenience on compression tools with a greater significance α> 0.05, namely 0.373 and a regression coefficient of 0.167 units or 16.7% positive value.